Safety and tolerability of linaclotide for the treatment of chronic idiopathic constipation and irritable bowel syndrome with constipation: pooled Phase 3 analysis. (3rd April 2019) - Nee, Judy W.; Johnston, Jeffrey M.; Shea, Elizabeth P.; Walls, Courtney E.; Tripp, Kenneth; Shiff, Steven; Fox, Susan M.; Bochenek, Wieslaw; Weissman, Darren; Currie, Mark G.; Lembo, Anthony J.
ABSTRACT: Background : Linaclotide is approved for treating irritable bowel syndrome with constipation (IBS-C; 290 µg QD) and chronic idiopathic constipation (CIC; 145 µg or 72 µg QD). These analyses aimed to assess linaclotide safety in a large, pooled Phase 3 population. Methods : In six randomized controlled trials (RCTs), patients received linaclotide (72 µg, 145 µg, 290 µg) or placebo daily for 12–26 weeks; in two long-term safety (LTS) studies, patients received open-label linaclotide for ≤78 additional weeks. Laboratory values, vital signs, and treatment-emergent adverse events (TEAEs) were assessed. Results : Overall, 3853 patients received ≥1 dose of linaclotide. The most common TEAE was diarrhea (majority [90.5% in RCTs] mild/moderate). Linaclotide patients experienced 1.1 diarrhea TEAE per patient-year in the RCTs (0.2 in placebo), and 0.3 in the LTS studies. In RCTs, 6.9% linaclotide and 3.0% placebo patients discontinued due to any adverse event (AE); 4.0% linaclotide and 0.3% placebo patients discontinued due to diarrhea. In LTS studies, 9.4% patients discontinued due to any AE, and 3.8% due to diarrhea. Serious AEs (SAEs) were rare and similar across treatment groups; there were no SAEs of diarrhea. Conclusion : These pooled analyses of patients treated for ≤104 weeks confirm linaclotide's overall safety.